2020
DOI: 10.14710/baf.5.1.2020.18-24
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Madu Lokal Berdasarkan Kadar Air, Gula Total dan Keasaman dari Kabupaten Magelang

Abstract: Madu merupakan cairan alami yang dihasilkan oleh lebah madu,berasal dari nektar bunga atau bagian lain dari tumbuhan. Madu dinyatakan memiliki kualitas baik apabila memenuhi standar kualitas madu. Kualitas madu dapat ditentukan berdasarkan kadar air, gula dan keasaman. Penelitian ini bertujuan untuk mengetahui kualitas madu lokal di Kabupaten Magelang. Pengambilan sampel secara purposive sampling dari lima wilayah Kabupaten Magelang, yaitu Desa Kaliurang, Ringinanom, Kaliabu, Munggangsari, danKebonrejo. Penent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Padjula [14] showed that the acidity levels found in klanceng honey range from 196.34 -200.34 ml NaOH/kg on the extraction times treatment, the extraction time used has an acidity value ranging from 156.67 -214.89 ml NaOH / kg. This result was not comparable to Adityarini, Suedy, and Darmanti [15], who showed data on the acidity of klanceng honey in the Kebonrejo area amounted to 271.00±50.82 ml NaOH/kg with the use of an extractor for 2 minutes. The treatment of rotation speed and length of extraction time showed very noticeable (P<0.01) to the acidity value.…”
Section: Aciditycontrasting
confidence: 89%
“…Padjula [14] showed that the acidity levels found in klanceng honey range from 196.34 -200.34 ml NaOH/kg on the extraction times treatment, the extraction time used has an acidity value ranging from 156.67 -214.89 ml NaOH / kg. This result was not comparable to Adityarini, Suedy, and Darmanti [15], who showed data on the acidity of klanceng honey in the Kebonrejo area amounted to 271.00±50.82 ml NaOH/kg with the use of an extractor for 2 minutes. The treatment of rotation speed and length of extraction time showed very noticeable (P<0.01) to the acidity value.…”
Section: Aciditycontrasting
confidence: 89%
“…Honey obtained from South Kalimantan has the lowest pH, which is 3.5. This research is in line with [31] that the pH of honey has a range of 3.2 to 4.5, while the results of Adityarini [20] research with a pH of 3.42 to 6.01.…”
Section: Honey Colorsupporting
confidence: 88%
“…This research is in line with [37] that bee species affect the sugar content in honey. Likewise, Adityarini [20] stated that the sugar content in honey is influenced by the type of bee and the source of the nectar. Several factors affect the levels of reducing sugars in honey, including water content, humidity and maturity of honey [27].…”
Section: Reducing Sugarmentioning
confidence: 99%
See 1 more Smart Citation
“…Honey, which has a high concentration of total sugar, can impede yeast growth. Honey with low sugar content can enhance fermentation owing to the presence of a diluted sugar solution, which facilitates the breakdown of sugar by yeast (Adityarini et al, 2020).…”
Section: Tabel IV Honey Activitymentioning
confidence: 99%